Sri Lanka : Request for Stand-By Arrangement -Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses a request from the Sri Lankan authorities for a Stand-By Arrangement (SBA). The proposed SBA (of 400 percent of quota or SDR1.65 billion) would aim to smooth adjustment to the external shock that has hit the country, restore health to the country's public finances, allow for greater exchange rate flexibility, address weaknesses in the financial system, and protect the most vulnerable from the burden of the needed adjustment. In addition, the IMF program will provide a basis for the authorities to approach donors for supporting a longer-term reconstruction program.